The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s13744-014-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Pylorus of Bombyx mori (Linnaeus) (Lepidoptera: Bombycidae)

Abstract: The pylorus is a segment of the hindgut of great morphological diversity, which is subdivided into the posterior interstitial ring, pyloric cone, and pyloric valve. There is no morphological information on Bombyx mori (L.) hybrids, which is an insect of economic interest to Brazil. Consequently, this study aimed to analyze the morphology of the pylorus of hybrid larvae of fifth instars of B. mori from crossbreeding of Chinese and Japanese races. These were anesthetized, and the pylorus was fixed and processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The morphology, histology, and physiology of the alimentary canal are all related to the feeding habits and the digestive and absorptive processes (Chen et al 2016). The alimentary canal of Lepidopteran larvae is typically a hollow cylindrical structure consisting of three main regions: the foregut, midgut, and hindgut (Baggio et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology, histology, and physiology of the alimentary canal are all related to the feeding habits and the digestive and absorptive processes (Chen et al 2016). The alimentary canal of Lepidopteran larvae is typically a hollow cylindrical structure consisting of three main regions: the foregut, midgut, and hindgut (Baggio et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The insect hindgut is responsible for water reabsorption and formation of feces (Levy et al 2004b(Levy et al , 2008. Baggio et al (2014) observed that the pyloric valve intima of Bombyx mori (Linnaeus) was very thin, an advantageous feature for the reabsorption of water and ions. Rigoni et al (2004) found a characteristic Lepidopteran cryptonephric excretory system in the hindgut of Diatraea saccharalis (Fabricius).…”
Section: Introductionmentioning
confidence: 99%
“…The main functions of the foregut are physical digestion, consisting of feeding, grinding, swallowing, and temporary storage of mulberry leaves. The hindgut is present in the midgut transition that is generally thought to reabsorb certain salts and amino acids from food residue to maintain water balance and/or osmotic pressure in the silkworm [5][6][7]. The midgut is the most important section and comprises approximately 78 percent of the total length of the digestive tube.…”
Section: Introductionmentioning
confidence: 99%